2021
DOI: 10.3171/2020.9.jns202781
|View full text |Cite
|
Sign up to set email alerts
|

A propensity-adjusted comparison of middle meningeal artery embolization versus conventional therapy for chronic subdural hematomas

Abstract: OBJECTIVEMiddle meningeal artery (MMA) embolization is a promising treatment strategy for chronic subdural hematomas (cSDHs). However, studies comparing MMA embolization and conventional therapy (surgical intervention and conservative management) are limited. The authors aimed to compare MMA embolization versus conventional therapy for cSDHs using a propensity-adjusted analysis.METHODSA retrospective study of all patients with cSDH who presented to a large tertiary center over a 2-year period was performed. MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 36 publications
3
35
2
Order By: Relevance
“…In this study, we found that the 1-year total hospital cost of MMA embolization was $32 000 lower than the cost of surgical treatment for cSDH after propensity adjustment. Furthermore, our previous studies have shown that MMA embolization is effective and is associated with fewer treatment failures when compared with surgical evacuation 14 15…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we found that the 1-year total hospital cost of MMA embolization was $32 000 lower than the cost of surgical treatment for cSDH after propensity adjustment. Furthermore, our previous studies have shown that MMA embolization is effective and is associated with fewer treatment failures when compared with surgical evacuation 14 15…”
Section: Discussionmentioning
confidence: 99%
“…Surgical evacuation is the current gold standard for treating large or symptomatic hemorrhages 4. However, many recent studies have shown that embolization of the middle meningeal artery (MMA) is effective in treating cSDH 5–17. Furthermore, embolization of the MMA has been associated with fewer treatment failures compared with surgical evacuation 13 15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rupture of these neo-vessels may further enlarge the hematoma ( Takizawa et al, 2016 ). Hence, eliminating the blood supply to the outer neomembrane by embolization of the MMA (eMMA) has been proposed as a minimally invasive treatment for CSDH ( Ban et al, 2018 ; Catapano et al, 2020 , 2021a , 2021b ). And several systematic reviews and a meta-analysis have shown promising results with MMA embolization, including low rates of complication and recurrence ( Haldrup et al, 2020 ; Ironside et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options for cSDH include surgery (15)(16)(17), observation and medications such as dexamethasone (12,(18)(19)(20) and endovascular obliteration of the meningeal artery (21)(22)(23)(24)(25). There have been numerous studies examining the different procedures.…”
Section: Figure 2 |mentioning
confidence: 99%